Program Home Visite Sebagai Penguatan Citra Positif RSI Sakinah Kabupaten Mojokerto - Diah Mita Kusuma Wardani; Ratnaningrum ZD; MIAH. Lailin (Lembaga Pengembangan Kinerja Dosen, 2025)
In the modern era, which demands high-quality healthcare services, public trust has become a critical element for the sustainability of hospitals. This study aims to identify the home visite program as a means of strengthening the positive image of RSI Sakinah in Mojokerto Regency. The research method employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation. Informants were selected using purposive sampling, consisting of the head of the hospital’s public relations division and patients who received the home visite service. The results showed that the home visite program successfully strengthened the positive image of RSI Sakinah in Mojokerto Regency through empathetic, responsive, and adaptive communication strategies tailored to the social, cultural, and educational backgrounds of patients. This personal approach fostered closer emotional connections between the hospital and its patients, thereby enhancing their loyalty and satisfaction. Quarterly evaluations demonstrated that this program effectively reduced the number of complaints significantly and reinforced the hospital's positive image. The practical implications of this study provide practical guidance for the management of RSI Sakinah to develop more structured communication strategies to strengthen long-term patient loyalty.